TRACE METALS CHARACTERISATION IN ENVIRONMENTAL MEDIA: A CASE STUDY OF CEMENT PRODUCTION AREA, EWEKORO, SOUTHWEST, NIGERIA - Majolagbe, A.O.; Yusuf, K.A.; Duru, A.E. (European Scientific Journal, ESJ, 2014)
Environmental quality deterioration resulting from increase in the level of potentially toxic metals is becoming more pronounced, thus raising the question on safety status of environment. Characterisation and impact assessment of trace metals in the environmental media including groundwater, top soils, and tree barks in the vicinities of West African Portland Cement Company factory mill, Ewekoro, Ogun State, Nigeria was undertaken. The environmental samples were analysed for trace metals employing flame atomic absorption spectrometry (FAAS). The concentration of Cu, Cd and Fe detected in the groundwater samples ranged from 0.026-0.082, 0.0038-0.004 and 0.003-0.035 (mg/L) respectively. The decreasing order of metals observed in the top soil samples is Fe > Pb >Ni >Cr >Cu > Cd, while the pattern of trace metals concentration analysed in tree barks samples is Fe > Cu > Cr >Pb >Ni > Cd. The saturated index of the groundwater samples were saturated to undersaturated with respect to sulphates; Cd (OH)2, CdSO4, Melanterite (FeSO4:7H2O), while samples were saturated to supersaturated with respect to Otavite (CdCO3) and Siderite (FeCO3). Quality indices employed in analyzing soil data include enrichment factor (EF), contamination factor (CF) and pollution load index (PLI). The EF indicates the build up of trace metals in the environment (soil) particularly Pb. The level of metals analysed are within the threshold limit set by the WHO health-based guideline for drinking water. Significant correlation was found to exist between Cd and Ni, Cr and Fe both in the tree bark and top soil samples, suggesting common source.